Śląsk i Czechy oczami magnata litewskiego. Osiemnastowieczny diariusz podróżny starosty wiłkomierskiego Benedykta Tyzenhauza = Silesia and the Czech Republic through the eyes of Lithuanian magnate. Eighteenth-century travel diary of starost of Wilkomierz Benedict Tyzenhauz - Ziober, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Travels through Europe among the nobility and magnates of the Crown and the Grand Duchy of Lithuania experienced its heyday in the seventeenth and eighteenth centuries. They had a various character: educational, therapeutic, or diplomatic. Many Lithuanian magnates by virtue of its financial resources decided on a long expeditions through the old continent and left after them travel reports rich in interesting descriptions of the surrounding reality. Such an example may be unknown until now the memories of the peregrination through Silesia of starost of Wilkomierz Benedict Tyzenhauz.
Keywords: Śląsk, Dolny; Czechy; pamiętnik; podróże - 18 w.; Tyzenhauz, Benedykt